Reactive molecular dynamics simulation on the disintegration of Kapton and Upilex-S during atomic oxygen impact - Qiao, Shiying; Jiang, Lixiang; Jiang, Haifu; Liu, Yuming; Xu, Yanlin; Jiao, Zilong; Cui, Naiyuan; Wang, Lu (Frontiers in Materials, 2023)
Polyimides are polymeric materials that are widely used in spacecraft applications owing to their unique properties. However, exposure to a low-Earth-orbit environment containing atomic oxygen (AO) results in the disintegration of polymeric materials on the surface of spacecraft, thereby affecting the lifespan. Along with the development of theoretical research, the reactive force-field (ReaxFF) interatomic potential has become a robust computational method for exploring, developing and optimizing the material properties.This study employs the ReaxFF reactive-force-field molecular dynamics simulation (ReaxFF MD) program to investigate and compare the performance of two typical polyimide materials, Kapton and Upilex-S, under the impact of AO. Various aspects such as variations in the temperature, mass loss, decomposition products, and damage propagation depth were examined. Although these materials have similar elemental composition(C/H/O/N), they have different structures. Our results indicate that AO is initially adsorbed on the surfaces of both Kapton and Upilex-S. The continuous impact of AO leads to chemical reactions between AO and Kapton/Upilex-S. Erosion proceeds from the surface toward the interior of the materials. Similar to the findings of Experiment 2 conducted by the Materials International Space Station, our results also reveal that Upilex-S exhibits a lower mass loss and erosion yield than Kapton under the same AO conditions. This difference is primarily attributed to the distinct molecular structures of both Kapton and Upilex-S. Our study could provide valuable technical support for the extensive application of Upilex-S in spacecraft.